Secular Trends of Children’s Physical Fitness and the Impact of the COVID-Pandemic for Years 2012 to 2023 - Tanja Eberhardt; Klaus Bös; Alexander Woll; Reinhold Kliegl; Claudia Niessner (Sports Medicine - Open)
Abstract Background Physical fitness is a key component in the development of an active lifestyle and a determinant of future health, particularly in childhood. The findings of physical fitness assessments enable evidence-based monitoring and the identification of long-term trends. The COVID-19 pandemic is an additional factor that can be considered in the analysis, as its influence is already known. The aim of our analysis was to comprehensively investigate secular trends with respect to the physical fitness of children before and during the pandemic. This study also serves to test whether Citizen Science projects can deliver results comparable to those obtained using traditional assessment formats while also documenting certain limitations of this approach. Methods Data on annual assessments conducted in the German federal state of Baden-Wuerttemberg were pooled from 12 cohorts starting in 2012. The analyses are based on 25,580 6–10 year-old children (M = 7.56, SD = 1.21 years; 12,575 girls) in our analysis. We estimated the effects of the COVID-19 pandemic using a regression discontinuity design within a linear mixed model. This enabled us to estimate pre-pandemic and pandemic trends, and to adjust for age, sex, and body constitution fixed-effect covariates and child and region as random factors. Results For the pre-pandemic cohorts, we found significant trends only slightly negative or positive trends in six of eight items. This suggests that the declining trend in physical fitness in children has been slowing down. The COVID-19 pandemic affected physical fitness negatively for six items (i.e., shift at critical date: 6 min Run, Jumping Sideways, Sit-Ups, Push-Ups; negative change from pre-pandemic to pandemic trends: 20 m Sprint, Standing Long Jump). There was no evidence for pandemic changes in balancing backwards and stand-and-reach items. Effects of age, sex, and body constitution replicated previous results. Conclusions Continuous monitoring of children’s physical fitness is essential, especially in the context of the COVID-19 pandemic. Such monitoring identifies positive and negative trends and provides evidence for the need of strategies and actions. It is particularly important to initiate systematic initiatives during childhood to promote physical fitness and reduce deficits, as this is the time when the foundations for an active and healthy lifestyle are laid.